1981
DOI: 10.1002/anie.198102651
|View full text |Cite
|
Sign up to set email alerts
|

Electrophilic Reactions of Aryl‐ and Heteroaryl(triniethyl)silanes with a Remarkable Nucleophilic Catalysis

Abstract: Of preparative importance and mechanistic interest are the reactions of aryl‐trimethylsilanes (1), in which X is an anion‐stabilizing substituent, with electrophiles in the presence of hard bases. The yields are good.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1981
1981
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Consequently, they can be employed as solvents in carbon−carbon bond-forming reactions . For example, silicon-containing nucleophiles, such as hypercoordinate siliconates , and allylsilanes, add to aldehydes in N , N -dimethylformamide (DMF) solutions. In the course of our research on the reactions of aldehydes with siliranes, we observed that DMF reacts with these strained silanes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, they can be employed as solvents in carbon−carbon bond-forming reactions . For example, silicon-containing nucleophiles, such as hypercoordinate siliconates , and allylsilanes, add to aldehydes in N , N -dimethylformamide (DMF) solutions. In the course of our research on the reactions of aldehydes with siliranes, we observed that DMF reacts with these strained silanes.…”
mentioning
confidence: 99%
“…18 The intermediacy of a pentacoordinate siliconate would also explain the greater reactivity of formamides over esters and alkyl aldehydes, because the reactivity trend parallels the basicity of the carbonyl oxygens. Coordination of the amide to the silirane would have two effects: the pentacoordinate siliconate 9 would become nucleophilic 3,7,14 and the formyl group would become activated for nucleophilic attack. 19 Carbon-carbon bond formation involving the intermediate 20 9 would require an organized transition state and would be consistent with the observed high stereoselectivity.…”
mentioning
confidence: 99%
“…Conversion of 2 to 3 via Protiodesilation/Friedel-Crafts acylation and/or Trifluoroacyldesilation (ipso) Substitution. By analogy to the reported ipso acyldesilation by acetyl chloride 23 and acetic anhydride, 24 the reaction of trifluoroacetic anhydride with 2, in the presence of aluminum chloride, was expected to give 3. When this reaction was tried, the major product was the trisubstituted 3,5-bis(trimethylsilyl)trifluoroacetophenone (7, see Scheme 4).…”
Section: Screening Of Potential Catalysts For the Conversion Of Pheny...mentioning
confidence: 87%
“…Thus, 2 has been reacted with acetyl chloride and aluminum chloride in carbon disulfide solvent to form 3-trimethylsilyl acetophenone in a yield of 44% . Another paper cites this reaction (with acetic anhydride) as occurring with ”excellent yields” …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation